Strategic Leadership For The Implementation of Three Values of Higher Education Performed by The Indonesian Defense University (IDU) In The 2015-2018 Period - Ahmad Gafuri Dohamid; Ma'ruf Akbar; Muchlis R. Luddin (IJHCM (International Journal of Human Capital Management), 2020)
This research will discuss about IDU’s management in strategic leadership to implement Three Values of Higher Education in the 2015-2018 period of time using qualitative method of research. The result obtained from the research show that in educational aspect, IDU has taken necessary strategic steps for IDU’s improvement. IDU manages the resources that are owned by IDU in academic aspect. IDU has done management processes according to the vision and mission during their time of leadership. In research department, the strategic leadership of IDU is not conducted optimally, especially when using and keeping the core competency. In community service, IDU is not capable in creating an innovation for the community. It is also found in the research that the biggest challenge that IDU has is regarding human resources. Most of the lecturers teach in IDU do not have defense background in their previous education.